ANALISA TINGKAT KESEHATAN PT BANK CENTRAL ASIA TBK PERIODE 2018-2022 - Hanif Agnar Ramadhan (2023)
The purpose of this paper is to determine the health level of Bank Central Asia seen from the RGEC approach consisting of Risk Profile, Good Corporate Governance, Earnings, and Capital and see the overall health level. The method used in this paper is descriptive quantitative. The results of this paper show that Bank Central Asia is in the "1" composite rating with a "very healthy" category in terms of Risk Profile, Good Corporate Governance, Earnings, and Capital.